The divertor region formation in the stellarator system “Yamator” - Lesnyakov, G.G. (Вопросы атомной науки и техники, 2017)
By imposing a certain optimum vertical magnetic field and using the equi-inclination law of helical conductors winding, regularizations have been carried out for the region of the edge closed magnetic surfaces and the divertor region in the configurations of the l = 1, m = 3 and m = 5 Yamators. Magnetic configuration modes have been found, at which the narrowest regions with stochastic behavior of magnetic field lines are formed close to the conditional separatrices.